INVESTIGATION OF ANTIOXIDANT ACTIVITY (IN VITRO) AND GAS CHROMATOGRAPHY-MASS SPECTROMETRY PROFILING OF PORTULACA OLERACEA L. AND PORTULACA GRANDIFLORA HOOK. EXTRACTS - AO, KINICHENKO (Asian Journal of Pharmaceutical and Clinical Research, 2019)
Objective: The aim of this research was to investigate the antioxidant activity (AOA) of the methanolic extracts of different parts of Portulaca oleracea and Portulaca grandiflora. Methods: The plant different parts were extracted with methanol. The methanolic extracts of both species were screened for 2,2-diphenyl-1- picrylhydrazyl radical scavenging abilities and researched by gas chromatography-mass spectrometry (GC-MS) analysis. Results: GC-MS analysis of P. oleracea root extract revealed the presence of 39 biologically active compounds. 32 biologically active compounds were identified in P. grandiflora root extract. Both extracts revealed the AOA. Conclusion: The results of the investigation could be useful for further pharmacological and phytochemical researches to assess the beneficial properties of both these species.